2021
DOI: 10.3390/agronomy11061115
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Allelopathic Effect of Essential Oil of Litsea pungens

Abstract: Natural plant resources with herbicidal activity may be substitutes for synthetic chemical pesticides, likewise aromatic plant extracts, especially essential oils. Essential oil from Litsea pungens has been proved to possess a strong antibacterial property. Interestingly, we found the essential oil also showed a strong allelopathic capacity. Therefore, in the present work, the chemical composition of the essential oil from the fruit of L. pungens was analyzed by gas chromatography–mass spectrometry (GC–MS). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Molecular docking is a virtual inspection known as an effective process to describe possible interactions between a bioactive molecule and a target enzyme. In recent years, numerous studies investigating the allelopathic effects of various EOs have demonstrated that these bio‐mixtures exert phytotoxic effects by inhibiting photosynthetic pigments, notably chlorophyll [79–81] . Following the demonstration of significant phytotoxicity induced by the REO, especially the fraction R 3 , on L. sativa seeds, the subsequent section aims to evaluate its potential impact on chlorophyll‘s photosynthetic stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular docking is a virtual inspection known as an effective process to describe possible interactions between a bioactive molecule and a target enzyme. In recent years, numerous studies investigating the allelopathic effects of various EOs have demonstrated that these bio‐mixtures exert phytotoxic effects by inhibiting photosynthetic pigments, notably chlorophyll [79–81] . Following the demonstration of significant phytotoxicity induced by the REO, especially the fraction R 3 , on L. sativa seeds, the subsequent section aims to evaluate its potential impact on chlorophyll‘s photosynthetic stage.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, numerous studies investigating the allelopathic effects of various EOs have demonstrated that these bio-mixtures exert phytotoxic effects by inhibiting photosynthetic pigments, notably chlorophyll. [79][80][81] Following the demonstration of significant phytotoxicity induced by the REO, especially the fraction R 3 , on L. sativa seeds, the subsequent section aims to evaluate its potential impact on chlorophyll's photosynthetic stage. Thus, it is intended in this part of the present work to dock the structures of the majority constituents of REO within the active pocket of the crystal structure of the enzyme protoporphyrinogen IX oxidase (PDB: 1SEZ), a key enzyme in the biosynthesis of chlorophyll.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Since we have not tested pure substances in this study, we cannot determine the exact input of each ingredient of EO on the observed effects. According to reported data for limonene, α -pinene, camphene, β -pinene, borneol, pulegone, carvacrol, thymol, p -cymene, and 1,8-cineole, there were suggestions for their allelopathy potential [ 65 , 74 , 75 ]. The latter authors used whole EO, and as is well known, the EOs are mixes of compounds and it is difficult to determine which compounds exactly have an herbicidal effect.…”
Section: Discussionmentioning
confidence: 99%
“…The two species were chosen for our growth experiments because of their uniform seedling emergence and high germination rates. For these reasons, they are frequently used as standard monocotyledonous and dicotyledonous plants, respectively, in allelopathic research [54][55][56][57].…”
Section: Plant Materialsmentioning
confidence: 99%